Citizenship and identity in a multinational commonwealth : Poland-Lithuania in context, 1550-1772 - Friedrich, Karin; Pendzich, Barbara M. (2009)
"This volume seeks to address the doubts harboured by the West about the ability of East Central European states to build modern democracies and tolerant societies after the expansion of the European Union eastwards."–Jacket.